Pengaruh Apresiasi Guru Kepada Murid Berdasarkan Teori Motivasi Al-Ghazali dan Abraham Maslow - Fahri, Muhammad Raja Iqbal; Fauzan, Mochammad Naufal; Arifudin, Muhammad Irfan; Gunawan, Jujun; Arifin, Bambang Samsul (CV. Rayyan Dwi Bharata, 2024)
This research aims to find out the influence of giving appreciation by teachers in increasing students' learning motivation. The method used in this research ismix methods or mixed methods, combining qualitative and quantitative research approaches. Qualitative approach by trying to provide descriptions, distributing questionnaires to students, teachers and also literature reviews carried out by researchers and then analyzed. The quantitative approach is by analyzing questionnaire data. This research was carried out at PGII 1 Bandung Junior High School, taken from two points of view of teachers and students carrying out the learning process, and the results of the questionnaire were presented in the form of diagrams and numbers, so that readers can easily understand them. The research results show that the teacher's role in providing appreciation has a big impact on children's motivation, in line with the theory put forward by al-Ghazali and Abraham Maslow. This can be seen from the survey results that 94.7% of students agree that giving appreciation to students can increase motivation in learning. Meanwhile, 89.5% of students stated that they were motivated to learn more after seeing the results of assignment assessments, exam assessment results and/or report card results which showed positive support from teachers in the form of grade appreciation in any form which could increase students' enthusiasm for learning and self-confidence.